Sample preparation, test and analysis method for powder sample XRD (X-Ray Diffraction) characterization
Powder samples were prepared and processed through hydrothermal synthesis and ultrasonic dispersion, which solved the problems of uneven preparation, unstable fixation and complex map interpretation in XRD test, and achieved high-precision XRD test results.
Patent Information
- Application Number
- CN202510010990.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
In XRD tests, powder samples have problems such as uneven preparation, unstable fixation and complex map interpretation, resulting in low measurement accuracy and errors.
NiS powder was prepared by hydrothermal synthesis method, and the particle size of the sample was uniform and fixed and stable by ultrasonic dispersion, vacuum drying, agate mortar grinding, glass sample tank leveling and X-ray powder diffractometer testing, and the particle size of the sample was uniform and fixed and stable, and the pattern analysis was carried out through limited element retrieval.
The uniform preparation and stable fixation of powder samples are achieved, the measurement accuracy and accuracy of XRD test are improved, and the diffraction peaks of different phases can be effectively distinguished.
Smart Images

Figure CN119804518A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sample analysis and preparation of detection technology, and in particular relates to a sample preparation, testing and analysis method for XRD characterization of powdered samples. Background Art
[0002] XRD is the abbreviation of X-ray diffraction, and its full name in Chinese is X-ray diffraction. It is a fast, accurate and efficient material non-destructive testing technology. As a means of characterizing crystal structure and its changing laws, it is mainly used for phase analysis, crystal texture analysis, stress testing, etc.
[0003] When X-rays interact with matter, their energy conversion is generally divided into three parts, one part is scattered, one part is absorbed, and one part continues to propagate along the original direction through the matter. When the scattered X-rays have the same wavelength as the incident X-rays, diffraction will occur on the crystal, that is, when the optical path difference caused by the crystal plane spacing is equal to an integer multiple of the wavelength. By comparing the unique diffraction pattern of each crystalline substance with the standard diffraction pattern, the physical phase present in the sample can be identified using the three-peak principle.
[0004] XRD can measure bulk and powder samples. All the information it obtains is based on the structure of the material. It is the main method for studying the phase and crystal structure of a substance. When a substance (crystalline or amorphous) is subjected to diffraction analysis, the substance is irradiated with X-rays to produce different degrees of diffraction. The material composition, crystal form, intramolecular bonding mode, molecular configuration, conformation, etc. determine the unique diffraction pattern produced by the substance.
[0005] X-ray diffraction method has the advantages of no damage to samples, no pollution, fast, high measurement accuracy, and the ability to obtain a large amount of information about crystal integrity. Therefore, X-ray diffraction analysis, as a modern scientific method for material structure and composition analysis, has gradually been widely used in research and production in various disciplines. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide an analytical method for XRD characterization of powdered samples. The main technical problems to be solved include the following: First, the preparation of powdered samples. It is necessary to ensure that the particle size and uniformity of the powder meet the requirements of the XRD (X-ray diffraction) test. If the powder particle size is too large, it will lead to inaccurate results such as broadening of the diffraction peak and abnormal intensity; uneven powder may make the composition and structural differences at different positions not reflected in the test or produce erroneous results; second, the placement and fixation of the sample during the test. The powdered sample is relatively loose, and it is necessary to find a suitable way to fix it on the test sample table to ensure that the sample position is stable during the test, and the measurement accuracy of the diffraction angle and intensity of the X-ray will not be affected by shaking or position changes; third, the accurate interpretation of the powder XRD spectrum. Since the powdered sample may contain multiple phases, a reliable analytical method is required to accurately determine the phase composition, crystal structure type, lattice parameters and other information; and it is necessary to be able to effectively distinguish the diffraction peaks of different phases, especially in complex situations where impurity phases or mixed phases exist.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] The present invention provides a sample preparation, testing and analysis method for XRD characterization of a powdered sample, comprising:
[0009] 1). NiS prepared by hydrothermal synthesis, pour the sample into the sample tube, and then put it into the ultrasonic disperser. During the ultrasonic process, avoid too long ultrasonic time to make the sample temperature too high. After repeated washing with deionized water and anhydrous ethanol, put it in a vacuum oven and dry it at 60℃ for 12h;
[0010] 2). Pour the sample in the sample tube into the agate mortar and grind the sample; the pestle head should be pressed on the mortar body, and a circular motion should be made along the lower part of the mortar, first slowly and then quickly. During the grinding process, use a medicine spoon to scrape the sample on the mortar wall and the pestle head into the mortar;
[0011] 3). Transfer the ground sample to the prepared glass sample tank in time, then take another cover glass, gently press the sample with the cover glass, then stack the glass sample holder and the slide together, gently knock it to one side on the test bench so that the sample is located on one side of the glass sample tank, repeat this several times to make the sample surface flat. Then scrape off the excess powder sample on the edge of the sample holder;
[0012] 4). Press the Door button on the diffractometer panel, the indicator light flashes, and you hear the sound of deflation. Slowly pull the diffractometer protection door to the right; install the sample surface upward on the sample stage. At this time, pay attention to place the sample in the center of the stage as much as possible, so that the slit is aligned with the sample; gently pull the right door to the left, and the two doors will automatically stick together, and then set the parameters on the computer test software;
[0013] 5). Click the Browse button to enter the file save dialog box. Set the file save location and sample name, return to the main interface, select the scanning range of 5°-80° and the test time of 4.5 minutes, and then start the test;
[0014] 6). After the test, the system automatically saves the data in .xrdml format. In order to facilitate importing into the drawing software for drawing, click Convert to convert it into .xy format data;
[0015] 7). Drag the data directly into the analysis software, use limited element search, select the specific category corresponding to the item you measured in Current Chemistry [Retrieval], click the OK button in the lower right corner to enter the element selection interface; after selecting Ni and S elements, click the OK button in the upper right corner; then proceed with the analysis.
[0016] Furthermore, the sample preparation process for XRD characterization of the powdered sample is as follows:
[0017] Use a medicine spoon to take an appropriate amount of sample and put it in the glass sample slot. Take another glass slide and gently press the sample with the slide. Then stack the glass sample holder and the slide together and gently knock it to one side on the test bench so that the sample is located on one side of the glass sample slot. Repeat this several times to make the sample surface flat. Then scrape off the excess powder sample on the edge of the sample holder and wipe it clean before testing.
[0018] Furthermore, the sample must be scraped flat and have the same height as the surface of the sample holder, otherwise it will cause deviations in the measurement angle and the corresponding d value.
[0019] Furthermore, the sample preparation process specifically includes:
[0020] 1). Drying: Put the powdered sample into a glass drying dish, put the glass drying dish into a vacuum drying oven, and dry it at a specified temperature until the mass of the sample no longer changes;
[0021] 2). Grinding: Suitable for powder materials that are easy to agglomerate and some brittle materials; for many bulk and brittle materials, directly use a clean pestle and mortar to grind them; during the grinding process, use a medicine spoon to scrape the sample on the mortar wall and pestle head into the mortar;
[0022] 3). Wipe the sample slot: clean the glass sample holder used for the test with alcohol cotton, and then blow dry with an ear cleaning bulb;
[0023] 4). Sample preparation: Use a medicine spoon to take an appropriate amount of sample and place it in the glass sample slot. Take another cover glass and gently press the sample with the cover glass. Then stack the glass sample holder and the slide together, and gently knock it to one side on the test bench so that the sample is located on one side of the glass sample slot. Repeat this several times to make the sample surface flat; then scrape off the excess powder sample on the edge of the sample holder, wipe it clean and start testing.
[0024] Furthermore, the sample amount should not be too small, which is 0.8-1.2 grams; try to make the powder sample cover the entire sample table; the sample particle size is generally required to be 10-80μm to avoid uneven particles; the sample should have sufficient strength and stability so as not to be damaged or changed under electron beam irradiation; it should not contain moisture or other volatile substances. Samples containing moisture or other volatile substances should be dried and removed first.
[0025] Furthermore, the model of the X-ray powder diffractometer used was German Bruker D8, and the test conditions were: the target material was graphite monochromatic Cu target Kα ray, The tube voltage was 40 kV, the tube current was 40 mA, the scanning range was 5°-80°, and the scanning rate was 5° / min. -1 .
[0026] Compared with the prior art, the beneficial technical effects of the present invention are:
[0027] The sample preparation is simple and basically does not require complicated pretreatment. It is a non-destructive test method. After the test is completed, the sample can basically remain intact and can also be used for other tests. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is the XRD spectrum. DETAILED DESCRIPTION
[0029] Below in conjunction with embodiment, the present invention is described in further detail:
[0030] This embodiment provides a sample preparation, testing and analysis method for XRD characterization of a powdered sample, including:
[0031] Specifically, for NiS powder prepared by hydrothermal synthesis, in order to determine its specific phase, it is necessary to perform XRD characterization analysis. The model of the X-ray powder diffractometer used in the present invention is German Bruker D8, and the test conditions are: the target material is graphite monochromatic Cu target Kα ray The tube voltage was 40 kV, the tube current was 40 mA, the scanning range was 5°-80°, and the scanning rate was 5° / min. -1 .
[0032] The sample preparation, testing and analysis process is as follows:
[0033] 1. NiS prepared by hydrothermal synthesis, pour the sample into the sample tube, and then put it into the ultrasonic disperser. During the ultrasonic process, avoid too long ultrasonic time to make the sample temperature too high. After repeated washing with deionized water and anhydrous ethanol, put it in a vacuum oven and dry it at 60℃ for 12h.
[0034] 2. Pour the sample in the sample tube into the agate mortar and grind it. The pestle head should be pressed on the mortar body, and a circular motion should be made along the lower part of the mortar, first slowly and then quickly. During the grinding process, use a medicine spoon to scrape the sample on the mortar wall and the pestle head into the mortar.
[0035] 3. Transfer the ground sample to the prepared glass sample tank in time, then take another cover glass, gently press the sample with the cover glass, then stack the glass sample holder and the slide together, gently knock it to one side on the test bench so that the sample is located on one side of the glass sample tank, repeat this several times to make the sample surface flat. Then scrape off the excess powder sample on the edge of the sample holder.
[0036] 4. Press the Door button on the diffractometer panel, the indicator light flashes, and you hear the sound of deflation. Slowly pull the diffractometer protection door to the right. Install the sample surface facing up on the sample stage. At this time, pay attention to place the sample in the center of the stage as much as possible, so that the slit is aligned with the sample. Gently pull the right door to the left. After the two doors are automatically sucked together, set the parameters on the computer test software.
[0037] 5. Click the Browse button to enter the Save File dialog box. After setting the file save location and sample name, return to the main interface, select the scanning range as 5°-80° and the test time as 4.5 minutes, and then start the test.
[0038] 6. After the test, the system automatically saves the data in .xrdml format. In order to facilitate importing into the drawing software for drawing, you need to click Convert to convert it into .xy format data.
[0039] 7. Drag the data directly into the analysis software, use limited element search, select the specific category corresponding to the item you measured in Current Chemistry [Retrieval], click the OK button in the lower right corner to enter the element selection interface. After selecting Ni and S elements, click the OK button in the upper right corner.
[0040] 8. After analysis, the seven diffraction peaks at 31.1°, 38.2°, 49.7°, 55.3°, 68.3°, 73° and 76.9° correspond to the (110), (021), (113), (300), (015), (214) and (205) crystal planes of Ni3S2 (JCPDS, No.44-1418). Therefore, the synthesized nickel sulfide is Ni3S2. Figure 1 shown.
[0041] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing, testing and analyzing powdered samples by XRD characterization, characterized in that: include: 1). NiS prepared by hydrothermal synthesis, the sample is poured into a sample tube, and then placed in an ultrasonic disperser. During the ultrasonic process, the ultrasonic time should be avoided to avoid excessively high sample temperature; after repeated rinsing with deionized water and anhydrous ethanol, it is placed in a vacuum oven and dried at 60°C for 12h; 2). Pour the sample in the sample tube into the agate mortar and grind the sample; the pestle head should be pressed on the mortar body, and a circular motion should be made along the lower part of the mortar, first slowly and then quickly. During the grinding process, use a medicine spoon to scrape the sample on the mortar wall and the pestle head into the mortar; 3). Transfer the ground sample to the prepared glass sample tank in time, then take another cover glass, gently press the sample with the cover glass, then stack the glass sample holder and the slide together, gently knock it to one side on the test bench so that the sample is located on one side of the glass sample tank, repeat this several times to make the sample surface flat; then scrape off the excess powder sample on the edge of the sample holder; 4). Press the Door button on the diffractometer panel, the indicator light flashes, and you hear the sound of deflation. Slowly pull the diffractometer protection door to the right. Install the sample surface facing up on the sample stage. At this time, pay attention to place the sample in the center of the stage as much as possible, and align the slit with the sample. Gently pull the right door to the left, and the two doors will automatically lock together, then set the parameters on the computer test software; 5). Click the Browse button to enter the file save dialog box. Set the file save location and sample name, return to the main interface, select the scanning range of 5°-80° and the test time of 4.5 minutes, and then start the test; 6). After the test, the system automatically saves the data in .xrdml format. In order to facilitate importing into the drawing software for drawing, click Convert to convert it into .xy format data; 7). Drag the data directly into the analysis software, use limited element search, select the specific category corresponding to the item you measured in Current Chemistry [Retrieval], click the OK button in the lower right corner to enter the element selection interface; after selecting Ni and S elements, click the OK button in the upper right corner; then proceed with the analysis.
2. The method for preparing, testing and analyzing powdered samples by XRD characterization according to claim 1, characterized in that: The sample preparation process for XRD characterization of the powdered sample is as follows: Use a medicine spoon to take an appropriate amount of sample and put it in the glass sample slot. Take another glass slide and gently press the sample with the slide. Then stack the glass sample holder and the slide together and gently knock it to one side on the test bench so that the sample is located on one side of the glass sample slot. Repeat this several times to make the sample surface flat. Then scrape off the excess powder sample on the edge of the sample holder and wipe it clean before testing.
3. The method for preparing, testing and analyzing powdered samples by XRD characterization according to claim 2, characterized in that: The sample must be scraped flat and at the same height as the surface of the sample holder, otherwise it will cause deviations in the measurement angle and the corresponding d value.
4. The XRD analysis method for powdered samples according to claim 1 or 2, characterized in that: The sample preparation process specifically includes: 1). Drying: Put the powdered sample into a glass drying dish, put the glass drying dish into a vacuum drying oven, and dry it at a specified temperature until the mass of the sample no longer changes; 2). Grinding: Suitable for powder materials that are easy to agglomerate and some brittle materials; for many bulk and brittle materials, directly use a clean pestle and mortar to grind them; during the grinding process, use a medicine spoon to scrape the sample on the mortar wall and pestle head into the mortar; 3). Wipe the sample slot: clean the glass sample holder used for the test with alcohol cotton, and then blow dry with an ear cleaning bulb; 4). Sample preparation: Use a medicine spoon to take an appropriate amount of sample and place it in the glass sample slot. Take another cover glass and gently press the sample with the cover glass. Then stack the glass sample holder and the slide together, and gently knock it to one side on the test bench so that the sample is located on one side of the glass sample slot. Repeat this several times to make the sample surface flat; then scrape off the excess powder sample on the edge of the sample holder, wipe it clean and start testing.
5. The method for preparing, testing and analyzing powdered samples by XRD characterization according to claim 4, characterized in that: The sample amount should not be too small, which is 0.8-1.2 grams; try to make the powder sample cover the entire sample table; the sample particle size is generally required to be 10-80μm to avoid uneven particles; the sample should have sufficient strength and stability so as not to be damaged or changed under electron beam irradiation; it should not contain moisture or other volatile substances. Samples containing moisture or other volatile substances should be dried and removed first.
6. The method for preparing, testing and analyzing powdered samples by XRD characterization according to claim 4, characterized in that: The model of the X-ray powder diffractometer used was the German Bruker D8. The test conditions were as follows: the target material was graphite monochromatic Cu target Kα ray, The tube voltage was 40 kV, the tube current was 40 mA, the scanning range was 5°-80°, and the scanning rate was 5° / min. -1 .
Citation Information
Cited By
Device and method for preparing filament XRD (X-Ray Diffraction) sample
CN121595608A